Evaluating the effect of selected plant extracts on Citrus mealybug, Planococcus citri (RISSO) (Homoptera: Pseudococcidae) attacked different Citrus cultivars in Kurdistan Region - Nawzad B. Kadir; Pshtiwan A. Jalil (Zanco Journal of Pure and Applied Sciences, 2024)
The plants Eucalyptus camaldulensis, Ocimum basilicum, Alhaji maurorum, and Mentha longifolia extracted in ethanol at different concentrations (0.5, 0.75, and 1%) were examined under laboratory conditions against Citrus mealybug, Planococcus citri (Risso) which is dangerous and widely distributed insects infesting most citrus cultivars in Iraq including Erbil province, Kurdistan region. The concentrations with the control (ethanol solvent only) were evaluated under laboratory conditions, and the lethal effectiveness of all extracts was examined after twelve and twenty-four hours of spraying. Data demonstrated that the Eucalyptus extracts and camel thorn grass had the highest reduction of the mealybug nymphs in both exposure times of spraying from treatment with the evaluated concentrations. The mortality effects of dark opal basil and mint extracts were also significant but in a mild manner. Exposure periods had a significant impact on the reduction of mealy bug nymphs too. The conclusions supported using of plant extracts as an alternative method to properly control this insect from the traditional chemical methods.